Proof -Based Learning Design Using APOS Theory on Triangle Inequality Theorem Material - Septiati, Ety; Hiltrimartin, Cecil; Hartono, Yusuf (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2023)
This research aims to produce a series of activities that can support evidence-based learning on the material of the Triangle Inequality Theorem. The research method used was design research type validation study and involved 22 4th semester students of the Mathematics Education study program at PGRI University Palembang. The research was conducted through 3 stages, namely preliminary design, design experiment and restropective analysis. Data collection was carried out using observation techniques, documentation and activity sheets. The research data were analyzed qualitatively, namely comparing the results of observations during the learning process with the HLT that had been designed. The results showed that the designed activities can support evidence-based learning for Triangle Inequality Theorem material.